2016
DOI: 10.1530/endoabs.43.oc7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of eye mask on sleep quality in patients of coronary care unit

Abstract: Objectives: Patients in coronary care unit (CCU) are at risk of sleep deprivation. This study investigated effects of eye mask on sleep quality in patients of CCU in Southeast of Iran by a cross-over design. Methods: Using Verran and Snyder-Halpern Sleep Scale (VSH Sleep Scale), quality sleep of 60 patients with and without usage of eye mask were evaluated. This tool consists of 16 items that includes three main sleep sub scales: disturbance, effectiveness, and supplementation. Results: In total, 34, 22 and 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
2
19
1
Order By: Relevance
“…The findings are consistent with the results of several studies conducted on the quality of sleep in ICU patients over the past three decades [25], [26]. Study of Mashayekhi et al on CCU patients demonstrated the short nighttime sleep-duration of the patients and the poor quality of sleep regarding efficiency and disturbance [27]. In intervention studies on the quality of sleep in ICU patients, the subject had poor sleep quality before the intervention, and controlling some environmental factors could improve the quality of sleep in the patients [2], [15], [28].…”
Section: Discussionsupporting
confidence: 89%
“…The findings are consistent with the results of several studies conducted on the quality of sleep in ICU patients over the past three decades [25], [26]. Study of Mashayekhi et al on CCU patients demonstrated the short nighttime sleep-duration of the patients and the poor quality of sleep regarding efficiency and disturbance [27]. In intervention studies on the quality of sleep in ICU patients, the subject had poor sleep quality before the intervention, and controlling some environmental factors could improve the quality of sleep in the patients [2], [15], [28].…”
Section: Discussionsupporting
confidence: 89%
“…Studies on non-pharmacological interventions such as aromatherapy ( 28 ) and use of eye masks ( 30 ) and pharmacological interventions such as the use of Escitalopram ( 27 ) showed positive results, in which there was a significant improvement in the sleep of the study patients.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed that patients had sleep disorders related to sleep disturbance, efficiency and supplementation. The use of masks caused an improvement in the subscale disturbance, with changes related to the item “wake up after the onset of sleep”; in the subscale efficiency, related to sleep quality and sleep adequacy assessment; and in the subscale supplementation, where the changes were related to “waking up after final excitement” ( 30 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Associated with this fact, the diagnostic inference of nurses considers cognitive aspects that cannot be reliably measured by instruments. Thus, instruments that evaluate sleep in a subjective way, such as self‐reports, questionnaires, and scales such as the VASS are effective, and have been used by other researchers (Bergamasco, ; Buysse, ; Mashayekhi, Pilevarzadeh, Amiri, & Rafiei, ).…”
Section: Discussionmentioning
confidence: 99%